2021
DOI: 10.26714/mki.4.2.2021.92-100
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Shift Hours and Its Effect on Quality of Life among Nurses: A Comparative Study

Abstract: In organizing health services in hospitals, the nursing team is the frontline for achieving service for 24 hours continuously, therefore in some division, like ICU or ER, nurses work with shift hours. There is some evidence of shift work’s psychological and physiological effects that can influence nurses' quality of life. This study aims to obtain an overview of the quality of life in nurses who work into the shift and its comparison with non-shift. This study was an online survey that involving nurses from ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…On the balance between private and professional life, we found that 53% of nursing staff believed their personal life suffers from their job. This observation aligns with the conclusions of researchers such as Pisarski [11] and Prameswari [13], suggesting complications in the personal life of shift workers. According to Kowitlawkul, Singaporean nurses on shift schedules spent more time at work than in their personal lives [14].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the balance between private and professional life, we found that 53% of nursing staff believed their personal life suffers from their job. This observation aligns with the conclusions of researchers such as Pisarski [11] and Prameswari [13], suggesting complications in the personal life of shift workers. According to Kowitlawkul, Singaporean nurses on shift schedules spent more time at work than in their personal lives [14].…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, the QWL of nurses is a multidimensional issue. Our findings, although inherent to our context, align with those of other researchers like Barrau-Baumstarck [20] and Prameswari [13], highlighting the crucial importance of work schedules in the QWL of healthcare staff and especially their negative impact on the quality of life both at work and outside of it for nurses working shift hours and night shifts [21,22].…”
Section: Discussionsupporting
confidence: 90%
“…This indicates some inconsistencies and unfair scheduling between nurses, which could lead to conflict and dissatisfaction. Moreover, having less free time to relax may lead to a lower quality of life among nurses [45].…”
Section: Resultsmentioning
confidence: 99%